BIOMEX experiment: ultrastructural alterations, molecular damage and survival of the fungus Cryomyces antarcticus after the Experiment Verification Tests - Pacelli, C.; Selbmann, L.; Zucconi, L.; de Vera, Jean Pierre Paul; Rabbow, Elke; Horneck, G.; de la Torre, R.; Onofri, S. (Origins of Life and Evolution of Biospheres, 2016)
The search for traces of extinct or extant life in extraterrestrial environments is one of the main goals for astrobiologists; due to their ability to withstand stress producing conditions, extremophiles are perfect candidates for astrobiological studies. The BIOMEX project aims to test the ability of biomolecules and cell components to preserve their stability under space and Mars-like conditions, while at the same time investigating the survival capability of microorganisms. The experiment has been launched into space and is being exposed on the EXPOSER2 payload, outside of the International Space Station (ISS) over a time-span of 1.5 years. Along with a number of other extremophilic microorganisms, the Antarctic cryptoendolithic black fungus Cryomyces antarcticus CCFEE 515 has been included in the experiment. Before launch, dried colonies grown on Lunar and Martian regolith analogues were exposed to vacuum, irradiation and temperature cycles in ground based experiments (EVT1 and EVT2). Cultural and molecular tests revealed that the fungus survived on rock analogues under space and simulated Martian conditions, showing only slight ultra-structural and molecular damage.